Clinical profile of a Polish cohort of children and young adults with cystinuria. Issue 1 (6th January 2021) - Tkaczyk, Marcin; Gadomska-Prokop, Katarzyna; Załuska-Leśniewska, Iga; Musiał, Kinga; Zawadzki, Jan; Jobs, Katarzyna; Porowski, Tadeusz; Rogowska-Kalisz, Anna; Jander, Anna; Kirolos, Merit; Haliński, Adam; Krzemień, Aleksandra; et al.
Abstract: Background: Cystinuria is an inherited disorder that results in increased excretion of cystine in the urine. It accounts for about 1–2% of pediatric kidney stones. In this study, we sought to identify the clinical characteristics of patients with cystinuria in a national cohort. Methods: This was a retrospective study involving 30 patients from the Polish Registry of Inherited Tubulopathies. Initial data and that from a 6-month follow-up were analyzed. Mutational analysis was performed by targeted Sanger sequencing and, if applicable, MLPA analysis was used to detect large rearrangements. Results: SLC7A9 mutations were detected in 15 children (50%; 10 males, 5 females), SLC3A1 mutations in 14 children (47%; 5 males, 9 females), and bigenic mutations in one male patient. The first clinical symptoms of the disease were detected at a median of 48 months of age (range 3–233 months). When individuals with different mutations were compared, there were no differences identified in gender, age of diagnosis, presence of UTI or urolithiasis, eGFR, calcium, or cystine excretion. The most common initial symptoms were urolithiasis in 26 patients (88%) and urinary tract infections in 4 patients (13%). Urological procedures were performed in 18 out of 30 (60%). Conclusions: The clinical course of cystinuria is similar among patients, regardless of the type of genetic mutation. Most patients require surgery before diagnosis or soon after it. Patients require combined urological and pharmacological treatment for prevention of stone recurrence and renal function preservation.